PEMBERDAYAAN MASYARAKAT DI LIMA DESA BERPRODUKSI BERAS RENDAH DI KECAMATAN BANYUDONO KABUPATEN BOYOLALI - Wijianto, Arip (Caraka Tani: Journal of Sustainable Agriculture, 2012)
Farmer dependence at district Banyudono regency Boyolali fertilizer use an-organic in agriculture cultivation day after day becoming more tall. While this region has potential enough tall for organic fertilizer maker, especially fertilizer bokashi. Straw and livestock dirt upon which fertilizer maker bokashi available enough overflow at this area. Rice production at village Denggungan, Ketaon, Bangak, Batan, and Ngaru-aru belong to low. One of the low cause rice productivity at five this villages more go down it power supports tune towards plants cultivation that caused by chemical fertilizer use continually. Method that used in this dedication training and assistance. Farmer group that taken in this dedication activity group with biggest member total and has broad tune at each village. Ability to make fertilizer bokashi self this is supposed can change farmer behavior to change from chemical fertilizer to organic fertilizer. Result that achieved in this dedication: (a) do fertilizer maker training bokashi towards farmer contact and successful farer at five villages concerned, (b) do continuation training in each farmer group, (c) a large part entrant has applied fertilizer bokashi in the agriculture tune. Obstacle that met in this dedication: (a) brown rice pest attack very great cause farmer fails harvest. This matter causes farmer doesn’t has straw and husk upon which standard fertilizer maker bokashi, (b) internal resistance: farmer aversion to a little strive to make fertilizer bokashi, because in such a way long coddled with fertilizer that live to wear. To overcome obstacles dedication team plans to continually do assistance and resuscitation to farmer about organic fertilizer applications urgency in their agriculture tune. Besides functioned to watch over agriculture tune fertility, organic fertilizer application can decrease pest attack and disease likes rice pest attack that cause farmer fails harvest until thrice MT.